The efficiency change of Italian public universities in the new millennium: a non-parametric analysis. Issue 3 (3rd July 2017) - Guccio, Calogero; Martorana, Marco Ferdinando; Mazza, Isidoro
Abstract : The paper assesses the evolution of efficiency of Italian public universities for the period 2000–2010. It aims at investigating whether their levels of efficiency showed signs of convergence, and if the well-known disparity between northern and southern regions decreased. For this purpose, we use a refinement of data envelopment analysis, namely window analysis, which allows for measuring efficiency in cross-sectional and time-varying data. We find that the efficiency of most universities registered only marginal changes in the period, although a notable re-ranking occurred. However, changes in the management of universities, consequential to the reform processes, did not affect the long-run tendencies, such as the persisting difference in performance between north and south.